2021
DOI: 10.1111/geb.13444
|View full text |Cite
|
Sign up to set email alerts
|

Ecogeographical patterns in owl plumage colouration: Climate and vegetation cover predict global colour variation

Abstract: Aim Ecogeographical rules link animal colours, especially those produced by melanin pigments, with variation in environmental conditions over wide geographical scales. In particular, Gloger’s rule, coined for endothermic animals in two versions, suggests that tegument darkness should increase at high temperature, as well as in highly humid environments. On the other hand, the thermal melanism hypothesis predicts that darker colourations should be more frequent in colder areas given their thermoregulation benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 71 publications
(154 reference statements)
0
18
0
Order By: Relevance
“…According to Gloger's rule, darker colours are associated with higher temperature and humidity and provide protection from solar radiation 53 . For example, Passarotto et al 54 found higher degrees of melanism (darker and redder colours) in owl plumage towards the equator, consistent with Gloger's rule. Other studies have found support for a role of pigmentation in protection from UV radiation (e.g.…”
Section: Discussionmentioning
confidence: 71%
“…According to Gloger's rule, darker colours are associated with higher temperature and humidity and provide protection from solar radiation 53 . For example, Passarotto et al 54 found higher degrees of melanism (darker and redder colours) in owl plumage towards the equator, consistent with Gloger's rule. Other studies have found support for a role of pigmentation in protection from UV radiation (e.g.…”
Section: Discussionmentioning
confidence: 71%
“…Our study adds a spatiotemporal complement to otherwise scarce studies linking microevolutionary patterns associated with climate change (Gienapp et al, 2008) and the emergence of Gloger's rule (Delhey, 2019;Delhey et al, 2020;Passarotto et al, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…The complex Gloger's rule has been explored insufficiently in birds and mammals. The few studies to date support patterns of geographical colour variation in crimson rosella ( Platycercus elegans ) [15], the variable antshrike ( Thamnophilus caerulescens ) [9], Furnariidae [8], Meliphagidae and Acanthizidae [78], Strigiformes [79] and feral pigs ( Sus scrofa ) [14]. A possible explanation in birds is that in warm and wet environments, dark feathers and pelage confer resistance to microbial degradation as melanin increases the abrasion resistance and keratin thickness [16,79].…”
Section: Discussionmentioning
confidence: 99%
“…The few studies to date support patterns of geographical colour variation in crimson rosella ( Platycercus elegans ) [15], the variable antshrike ( Thamnophilus caerulescens ) [9], Furnariidae [8], Meliphagidae and Acanthizidae [78], Strigiformes [79] and feral pigs ( Sus scrofa ) [14]. A possible explanation in birds is that in warm and wet environments, dark feathers and pelage confer resistance to microbial degradation as melanin increases the abrasion resistance and keratin thickness [16,79]. Darker colours are also selected in low-light environments due to dense vegetation favouring crypsis [8,80,81].…”
Section: Discussionmentioning
confidence: 99%